Chiral separation of tamsulosin by capillary electrophoresis - Maier, Vítězslav; Horáková, Jana; Petr, Jan; Tesařová, Eva; Coufal, Přemysl; Ševčík, Juraj (Journal of pharmaceutical and biomedical analysis, 2005)
Enantiomers of (+/-) 5-[2 (R,S)-{[2-(o-ethoxyphenoxy) ethyl] amino} propyl]-2-methoxy-benzenesulfonamide (tamsulosin, drug frequently used in the treatment of prostate diseases) were separated by capillary electrophoresis (CE). An acidic background electrolyte (BGE) with sulfated-beta-cyclodextrin (S-beta-CD) was used to create a chiral separation environment. Baseline separation of the isomers was achieved during 5 min using cathodic electro-osmotic flow (EOF) (countercurrent mode). The quantification limits were 5.3 x 10(-6) moll(-1) for R-isomer and 5.7 x 10(-6) moll(-1) for S-isomer. The R.S.D. values of peak area were 0.54% for R-isomer and 0.75% for S-isomer. The results achieved enable determination of 0.5% of optical impurity.
Keywords: alfa blokátory; Chromatography, High Pressure Liquid; furany; beta-Cyclodextrins; stereoizomerie; Electrolytes; osmóza; Electrophoresis; Electrophoresis, Capillary; Acetonitriles; chemické modely; Furans; Dose-Response Relationship, Drug; sulfonamidy; financování organizované; Financing, Organized; Adrenergic alpha-Antagonists; Stereoisomerism; elektroforéza kapilární; reprodukovatelnost výsledků; časové faktory; elektroforéza; beta-cyklodextriny; Models, Chemical; Reproducibility of Results; kyselina octová; elektrolyty; Acetic Acid; Sulfur; acetonitrily; síra; vztah mezi dávkou a účinkem léčiva; Osmosis; Time Factors; kalibrace; vysokoúčinná kapalinová chromatografie; Sulfonamides; Calibration